The Improvement of Learning in Motion and Force Topics using Cooperative Learning Model - Sukarti Sukarti (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
This study aims to increase students’ knowledge and understanding of motionand force. Each individual does not know exactly which material will be given at the beginning of the effective learning process that is appropriate and not difficult through the Cooperative Learning Model Method with a quantitative descriptive research approach. Classroom Action Research (CAR) is a way of determining how to do it in cycles. Both cycles, this method of obtaining data is known as the data collection method. Research subjects were seventh grade of C, totaling 35 students at the SMPN 4 Sungai Raya. There were 24 students with a percentage of 68% and continued Cycle II with improvements in planning and implementation accurately and properly using the Cooperative Learning Model in depth can only be said to have 33 students passed among 35 students with a percentage of 94%, 6% or 2 students who have not has passed. Through the implementation of cooperative learning model, the students can understand motion and force concepts well.